Transfer Structure In Buildings: Concept, Forms & Structural Behavior (Damascus University Journal for engineering sciences, 2024)
A transfer structure (TS) is a structure that alters the load path of the gravity loads, shifting the traditional path to  a different vertical alignment. (TS) are introduced in contemporary  buildings that feature multi-use functions or new forms and complex shapes, where TSs provide structural solutions that help architects making their ideas in  correct ways. The main idea of ​​the research came up  from the researchers’ observation of the local  architectural scenery in Syria  (whether in the academic field or the professional one ), where (TS) potentialities  are ignored, and rejected while it is considered  as an important  structural solution, with a  great  role on  enriching the architectural ideas and a structural solutions. The research consists of two parts: The first part provides an integrated presentation of the most important structural elements used in (TS) , diversion of loads, their forms and building materials .The second part deals with a statistical research to investigate the general local understanding of the concept of transfer structure in the case  of the Syrian  Engineers community  (architects and structural engineers ), Which adopted the hypothesis of the deficiency in the basic concepts of these structures and the search for the most important preferences and methods necessary to enhance the cognitive concept among  engineering community in general.
Keywords: Transfer Structure; Multi; Use Buildings; Tall Buildings